2016
DOI: 10.1016/j.amjsurg.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of surgical care in a high-volume center improves survival in resected pancreatic head cancer

Abstract: Background Durable clinical gains in surgical care are frequently reliant on well-developed standardization of practices. We hypothesized that the standardization of surgical management would result in improved long-term survival in pancreatic cancer. Methods Seventy-seven consecutive, eligible patients representing all patients who underwent PD and received comprehensive, long-term postoperative care at the University of Florida were analyzed. Patients were divided into pre- and post-standardization groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To our knowledge, this study is one of the first to evaluate temporal trends in the regionalization of RPS surgery to HVHs compared with PC, an explicitly regionalized cancer surgery. 14,15,17,20,26,[33][34][35] Although regionalization to HVHs has certainly begun for RPS, we have illustrated a significant lag in this time trend behind surgery for PC. Our findings have also reinforced previous studies that have demonstrated that high operative RPS volume yields improved surgical outcomes, 23 thus confirming that the benefits of regionalization parallel those of other complex cancers.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this study is one of the first to evaluate temporal trends in the regionalization of RPS surgery to HVHs compared with PC, an explicitly regionalized cancer surgery. 14,15,17,20,26,[33][34][35] Although regionalization to HVHs has certainly begun for RPS, we have illustrated a significant lag in this time trend behind surgery for PC. Our findings have also reinforced previous studies that have demonstrated that high operative RPS volume yields improved surgical outcomes, 23 thus confirming that the benefits of regionalization parallel those of other complex cancers.…”
Section: Discussionmentioning
confidence: 90%
“…A more recent study by Lidsky et al (24) covering the years up to 2012 agreed with these authors that lower number of lymph nodes were detected in LVCs than in HVCs. Standardization of pathology reporting has been shown to improve the quality of the analysis of PRs (38).…”
Section: Resultsmentioning
confidence: 99%
“…2 -4 Despite these figures, in contemporary series the average duration of hospital stay after PD has reduced to 7-9 days, 5 which is mainly due to a combination of centralization and increased use of enhanced recovery after surgery (ERAS) pathways. 6 Emergency hospital readmission after elective surgery, including after PD, is a major problem for healthcare organisations worldwide, and carries a significant financial burden. 7 Hospital readmission has been reported as an important measure of health care quality, 7,8 and is considered to be a 'failed discharge' by the U.K. National Health Service (NHS).…”
Section: Introductionmentioning
confidence: 99%